Condylar Position in the Treatment of Obstructive Sleep Apnea with a Mandibular Advancement Device: A Pilot Study - Gurgel, Marcela; Kurita, Lucio; Fonteles, Cristiane; Ribeiro, Thyciana; Costa, Fabio; Freitas, Benedito; Bruin, Veralice; Cevidanes, Lucia; Chaves-Junior, Cauby (Sleep Science, 2023)
Objective To evaluate, through a tomographic analysis, the positional changes of the condyle when using a mandibular advancement device (MAD) for the treatment of obstructive sleep apnea (OSA), and to assess if the condylar positions influence OSA polysomnographic patterns.Materials and Methods Ten OSA patients underwent treatment with an MAD, and polysomnographic and tomographic examinations were performed before therapy (T0) and after MAD placement (T1).Results By comparing the T0 and T1 measurements, we observed advancement and extrusion of the condyles in all patients (p < 0.001), as well as a decrease in the apnea-hypopnea index (AHI) (p < 0.001), increases in the mean (p = 0.001) and minimum (p < 0.001) oxyhemoglobin saturation, and a significant correlation between the anterior displacement of the right (p = 0.003) and left (p = 0.015) condyles.Discussion Condylar advancement was directly correlated with OSA improvement: the greater the advancement, the better the AHI.
Keywords: obstructive sleep apnea; mandibular advancement; mandibular condyle; cone-beam computed tomography